Sildenafil Enhances the Anticancer Activity of Paclitaxel in an ABCB1-Mediated Multidrug Resistance Xenograft Mouse Model (Journal of Cancer Research Updates, 2014)
The overexpression of ATP-binding cassette (ABC) transporters can produce multidrug resistance (MDR) in cancer cells. Previous in vitro studies from our group reported that sildenafil significantly inhibits the efflux function of the ABCB1/P-glycoprotein transporter in vitro. This investigation examined the effect of sildenafil on the ABCB1 transporter-mediated MDR in vivo. A nude mouse ABCB1 overexpressing-xenograft model was used to examine the effect of sildenafil in vivo. The concentration of paclitaxel in tumors and plasma was analyzed using high performance liquid chromatography (HPLC). Sildenafil attenuated tumor growth synergistically, and this occurred without significant weight loss or other overt phenotypic changes. The action of sildenafil can be attributed to the inhibition of the ABCB1-mediated drug efflux, thereby increasing the concentration of paclitaxel in ABCB1-overexpressing tumors. The potentiation of the pharmacologic action of paclitaxel by sildenafil suggests that it may be useful in treating cancers that overexpress the ABCB1 transporter.